Interendothelial Junctions and their Role in the Control of Angiogenesis, Vascular Permeability and Leukocyte Transmigration - Dejana, Elisabetta; Spagnuolo, Raffaella; Bazzoni, Gianfranco (Thrombosis and Haemostasis, 2001)
Endothelial cell-cell junctions play an important role in vascular hemostasis. The two junctional proteins VE-cadherin and JAM-1 are localized at adherens and tight junctions, respectively. VE-cadherin is only expressed by endothelial cells, suggesting that it can exert cell specific function. Absence of VE-cadherin or blocking of its adhesive activity prevents a normal organization of new vascular structures, suggesting that VE-cadherin may be a molecular target of antiangiogenic therapy. In addition, the ability of permeability-increasing agents and adherent leukocytes to modify VE-cadherin/catenin organization may be related to a role in the control of vascular permeability and leukocyte infiltration. JAM-1 is an integral membrane protein expressed in endothelial and epithelial cells. Its extracellular domain can dimerize and bind homophilically. The intracellular domain (and in particular a PDZ-binding motif) enables JAM-1 to interact with structural and signaling proteins. Study of the molecular interactions of JAM-1 may help explain mechanisms of JAM-mediated function, such as control of paracellular permeability and leukocyte transmigration.
Keywords: Endothelium; angiogenesis; permeability; inflammation; adherens and tight junctions